(untitled) (The Strategic Review for Southern Africa, 2020)
The following arguments are in support of a “renegotiation of the terms of knowledge production” (Horáková 2016: 47). By doing so, this essay sides with demands by others (for example, Keim et al 2014) that “the need to move towards non-hegemonic forms of cooperation between academic realms and forms of knowledge is a practical-material as well as an intellectual task”, while “no success can be achieved without relentless criticisms on inhered spurious certainties” (Lagos 2015). Last but not least, this reasoning is influenced by the conviction that ‘neutral’ knowledge in a value-free vacuum detached from social interests does not exist: “ways of knowing and resulting bodies of knowledge are always historical and they are deeply political” (Bliesemann and Kostic 2017: 6). By pointing to the relevance of hierarchical structures and power, this essay concurs with Halvorsen (2016: 303) that, “the academic profession must rid itself once and for all of the notion that knowledge is invariably ‘positive’, that every question has one correct answer (the truth), and that this is to be obtained through one correct method”. After all — … knowledge of Africa has been produced within what we might define as a Western episteme. The theoretical, conceptual and methodological resources through which Africa is to this day rendered visible and intelligible speak from a place, about that place and in accordance with criteria of plausibility that use that particular place as the normative standard for truth (Macamo 2016: 326). I concur with Smith (1999) that true decolonisation is supposed to be concerned with having a “(m)ore critical understanding of the underlying assumptions, motivations and values that inform research practices” (Wilson 2001: 214). This is a necessary reminder that we should always include critical reflections when interStrategic Review for Southern Africa, Vol 40, No 1 Henning Melber rogating our own internalised value systems, which we often tend to understand and apply unchallenged as the dominant (if not only) norm.